Haemodialysis Alters the Index of Cardiac-Electrophysiological Balance - Arshad, Abdul Rehman; Khan, Tayyaba; Siddiqi, Fuad Ahmad; Tahir, Shabana; Ahmad, Shahid; Qayyum, Mohsin (Pakistan Armed Forces Medical Journal, 2022)
Objective: To study electrocardiographic changes during haemodialysis and determine the relationship between electrolyte alterations and acid-base balance.Study Design: Cross-sectional analytical study.Place and Duration of Study: Haemodialysis Unit, Combined Military Hospital, Peshawar Pakistan, from Jun to Jul 2022.Methodology: Adult patients with end-stage renal disease on maintenance hemodialysis were selected by convenience sampling. Exclusion criteria included current hospitalization, chest pain during haemodialysis, intra-dialytic hypotension,atrial fibrillation, pericardial effusion, shortening of haemodialysis sessions and unwillingness to participate in the study.Twelve lead electrocardiograms were recorded immediately before the start and end of haemodialysis sessions. At the same time, serum urea, creatinine, potassium, calcium and phosphate were measured. Bicarbonate levels were assessed by venous blood gas analysis. In addition, measurements for heart rate and durations of the PR interval, QRS complex, QT interval andcorrected QT interval reported by ECG machine software were recorded.Results: There were 35 patients with a mean age of 48.69±11.39 years. Duration of QRS complex increased from 92.83±9.98 to 100.00± 17.94 seconds after haemodialysis (p=0.017). Changes in other parameters were insignificant. QT/QRS and QTc/QRS ratios reduced by 0.27±0.62 and 0.31±0.62 after haemodialysis (p=0.014 and 0.005, respectively). Changes in none of the biochemical parameters during haemodialysis could predict the reduction in QT/QRS or QTc/QRS ratios.Conclusion: The reduction in the index of cardiac electrophysiological balance during hemodialysis was not related to intradialytic changes in different electrolytes or base content.